Penyusunan Peraturan Negeri Haruku Tentang Pengelolaan Sumber Daya Wilayah Pesisir - Julista Mustamu; Yohanis Pattinasarany; Mahrita A. Lakburlawal (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Devotion to the Preparation of Haruku State Regulations Concerning the Management of Coastal and Marine Resources is an activity to form a state regulation so that all interests related to the Management of Coastal and Marine Areas Resources are accommodated and the creation of a regulation that creates harmony between communities.Purposes of Devotion: To produce a State Regulation product that regulates and organizes life in Haruku Country so that the people who are governed by the law obtain certainty, benefit and justice in the life of the state and society, especially in the Management of Coastal and Marine Area Resources. Method of Devotion: Activities are carried out using the method of compiling laws and regulations, especially the formation of village/traditional village legal products.Results of the Devotion: Preparation of state regulations as a form of practicing the principle of a welfare state where in Law No. 6 of 2014 concerning villages gives authority to villages to manage their own natural resources, both resources in mountainous areas and at sea. but then there are often various villages that find it difficult to manage their resources especially when you see that there are so many resources that exist in the sea and coastal areas starting from the abundance of fish, coral reefs, agar-agar and there are still many marine biota that must be managed properly by the people in In a country, this happens due to the lack of a clear regulation regarding the management of resources in coastal and marine areas as a benchmark, namely in one of the areas in Maluku, namely Haruku country, which does not yet have state regulations regarding the management of coastal and marine areas. So it is considered important. there is a state regulation that provides guarantees and guidance for the country in managing resources in coastal and marine areas as well as the intended state regulations giving authority, therefore in order to make these regulations, a Haruku country needs guidance in carrying out the preparation of these state regulations.